Modulation of IMD, Toll, and Jak/STAT Immune Pathways Genes in the Fat Body of Rhodnius prolixus During Trypanosoma rangeli Infection - Rolandelli, Agustín; Nascimento, Adeisa E. C.; Silva, Leticia S.; Rivera-Pomar, Rolando; Guarneri, Alessandra A. (Frontiers in Cellular and Infection Microbiology, 2021)
Trypanosoma rangeli is the second most common American trypanosome that infects man. It is vectored by triatomines from the genus Rhodnius, in which it invades the hemolymph and infects the salivary glands, avoiding the bug immune responses. In insects, these responses are initiated by well conserved pathways, mainly the IMD, Toll, and Jak/STAT. We hypothesize that long-term infection with T. rangeli in the gut or hemolymph of Rhodnius prolixus triggers different systemic immune responses, which influence the number of parasites that survive inside the vector. Thus, we investigated groups of insects with infections in the gut and/or hemolymph, and evaluated the parasite load and the expression in the fat body of transcription factors (Rp-Relish, Rp-Dorsal, and Rp-STAT) and inhibitors (Rp-Cactus and Rp-Caspar) of the IMD, Toll, and Jak/STAT pathways. We detected lower parasite counts in the gut of insects without hemolymph infection, compared to hemolymph-infected groups. Besides, we measured higher parasite numbers in the gut of bugs that were first inoculated with T. rangeli and then fed on infected mice, compared with control insects, indicating that hemolymph infection increases parasite numbers in the gut. Interestingly, we observed that genes from the three immune pathways where differentially modulated, depending on the region parasites were present, as we found (1) Rp-Relish downregulated in gut-and/or-hemolymph-infected insects, compared with controls; (2) Rp-Cactus upregulated in gut-infected insect, compared with controls and gut-and-hemolymph-infected groups; and (3) Rp-STAT downregulated in all groups of hemolymph-infected insects. Finally, we uncovered negative correlations between parasite loads in the gut and Rp-Relish and Rp-Cactus expression, and between parasite counts in the hemolymph and Rp-Relish levels, suggesting an association between parasite numbers and the IMD and Toll pathways. Overall, our findings reveal new players in R. prolixus–T. rangeli interactions that could be key for the capacity of the bug to transmit the pathogen.